Positive electrode material and lithium ion secondary battery

The use of a positive electrode material with multiple lithium alloys and a positive electrode active material, forming a composite, addresses the issue of capacity loss in lithium-ion batteries by controlling dendrite growth and maintaining battery performance over cycles.

JP2025063748AActive Publication Date: 2025-04-16TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023173185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16
Estimated Expiration
2043-10-04

AI Technical Summary

Technical Problem

In lithium-ion secondary batteries, the incorporation of lithium alloys into the positive electrode leads to metal ions migrating to the negative electrode, forming resistive layers and causing a decrease in battery capacity.

Method used

A positive electrode material comprising a combination of a positive electrode active material and two or more types of lithium alloys, where the lithium alloys have an alloying potential of 0.5V (vs.Li/Li) or more, and include metal elements such as bismuth, tin, and antimony, which form a composite with the positive electrode active material.

Benefits of technology

This configuration effectively suppresses the initial decrease in battery capacity and the degradation due to repeated charge and discharge cycles, by slowing down the growth of dendrites and preventing short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063748000001
    Figure 2025063748000001
  • Figure 2025063748000002
    Figure 2025063748000002
Patent Text Reader

Abstract

To provide a positive electrode material capable of manufacturing a lithium ion secondary battery in which the initial decrease in battery capacity is suppressed and the decrease in battery capacity due to repeated charging and discharging is suppressed, as well as a lithium ion secondary battery manufactured using the positive electrode material.SOLUTION: A positive electrode material includes a positive electrode active material and two or more kinds of lithium alloys, each of which contains a metal element having an alloying potential with lithium of 0.5 V (vs. Li / Li+) or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode material and a lithium ion secondary battery. [Background technology]

[0002] In lithium-ion secondary batteries, some of the lithium ions released from the positive electrode active material during the initial charge react with the electrolyte on the surface of the negative electrode, forming a coating called SEI (Solid Electrolyte Interphase). The consumption of lithium ions accompanying the formation of the SEI is desirably as small as possible because it causes a decrease in battery capacity. As a measure for suppressing the consumption of lithium ions accompanying the formation of the SEI, it has been proposed to include a lithium alloy in the positive electrode together with the positive electrode active material, and to compensate for the amount of lithium ions consumed in the formation of the SEI with lithium ions released from the lithium alloy during the initial charge (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2021-520614 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the method of incorporating a lithium alloy in the positive electrode, metal ions from the lithium alloy that has lost its lithium ions migrate to the negative electrode side and precipitate, and this precipitate may form a resistive layer, resulting in a decrease in battery capacity. An object of the present disclosure is to provide a positive electrode material capable of producing a lithium ion secondary battery in which the decrease in initial battery capacity is suppressed and the decrease in battery capacity due to repeated charging and discharging is suppressed, and a lithium ion secondary battery produced using this positive electrode material. [Means for solving the problem]

[0005] Means for solving the above problems include the following embodiments. <1> A positive electrode active material and two or more types of lithium alloys are included, The two or more types of lithium alloys have an alloying potential with lithium of 0.5V (vs. Li / Li + ) or more. <2> The metal element is selected from bismuth, tin and antimony; <1> The positive electrode material according to claim 1, <3> At least two of the lithium alloys contain metal elements having different crystal orientations. <1> or <2> The positive electrode material according to claim 1, <4> At least a portion of the positive electrode active material and at least a portion of the lithium alloy form a composite. <1> ~ <3> 13. The positive electrode material according to claim 12 . <5> The alloying potential between the positive electrode active material and lithium is 0.5V (vs. Li / Li + ) or more metal elements. Effect of the Invention

[0006] According to one embodiment of the present disclosure, there is provided a positive electrode material capable of producing a lithium ion secondary battery in which the decrease in initial battery capacity is suppressed and the decrease in battery capacity due to repeated charging and discharging is suppressed, and a lithium ion secondary battery produced using this positive electrode material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of multiple substances, unless otherwise specified.

[0008] <Cathode materials> The positive electrode material of the present disclosure is A positive electrode active material and two or more types of lithium alloys are included, The two or more types of lithium alloys have an alloying potential with lithium of 0.5V (vs. Li / Li + ) or more of the metal elements.

[0009] As will be shown in the examples described later, a secondary battery manufactured using the positive electrode material of the present disclosure suppresses the decrease in battery capacity due to repeated charging and discharging, even if the positive electrode contains a lithium alloy. One possible reason for this is that the growth direction of dendrites composed of two or more metal elements derived from the lithium alloy generated at the negative electrode is more likely to diffuse than that of dendrites composed of a single metal element, and the growth rate of the dendrites is slower. Suppressing the growth rate of dendrites is also effective in preventing the dendrites from breaking through the separator and causing a short circuit.

[0010] (Lithium alloy) Lithium alloys have an alloying potential of 0.5V (vs. Li / Li + ) or more. The above-mentioned alloying potential of the metal elements contained in the lithium alloy effectively compensates for the loss of lithium ions that are released from the positive electrode active material and consumed for the formation of the SEI during the initial charge of the battery, and as a result, the decrease in the initial battery capacity is effectively suppressed. The alloying potential with lithium is 0.5V (vs. Li / Li +) or more include bismuth (Bi, alloying potential: 0.81 to 0.83 V), tin (Sn, alloying potential: 0.57 to 0.66 V), and antimony (Sb, alloying potential: 0.94 to 0.96 V).

[0011] Examples of combinations of two or more types of lithium alloys contained in the positive electrode material include a combination of a lithium alloy containing Bi (hereinafter also referred to as a Li-Bi alloy) and a lithium alloy containing Sb (hereinafter also referred to as a Li-Sb alloy), a combination of a Li-Bi alloy and a lithium alloy containing Sn (hereinafter also referred to as a Li-Sn alloy), and a combination of a Li-Bi alloy, a Li-Sb alloy, and a Li-Sn alloy.

[0012] A specific example of the Li-Bi alloy is Li3Bi. A specific example of the Li-Sb alloy is Li3Sb. A specific example of the Li-Sn alloy is LiSn.

[0013] The positive electrode material preferably contains, as two or more types of lithium alloys, a Li-Bi alloy and at least one of a Li-Sb alloy and a Li-Sn alloy, and more preferably contains at least a Li-Bi alloy and a Li-Sb alloy. From the viewpoint of diffusing the growth direction of dendrites, lithium alloys containing metal elements with different crystal orientations may be combined. The crystal orientation of Bi is trigonal, the crystal orientation of Sn is tetragonal (cubic), and the crystal orientation of Sn is trigonal.

[0014] From the viewpoint of sufficiently compensating for the consumption of lithium ions accompanying the formation of the SEI, the total content of the two or more types of lithium alloys contained in the positive electrode material is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the positive electrode active material. From the viewpoint of ensuring sufficient energy density, the total content of the two or more types of lithium alloys contained in the positive electrode material is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of the positive electrode active material.

[0015] Regarding the proportion of each lithium alloy in two or more types of lithium alloys, for example, the content of the lithium alloy with the smallest content in the entire lithium alloy is preferably 10 mass% or more, more preferably 15 mass% or more, and even more preferably 20 mass% or more.

[0016] The lithium alloy may be in the form of particles. The volume average particle size of the lithium alloy in the form of particles is not particularly limited and can be selected, for example, within the range of 1 μm to 50 μm.

[0017] In the present disclosure, the volume average particle size of particles is the value at which the cumulative volume is 50% (D50) in the volume-based particle size distribution measured by a laser diffraction / scattering method.

[0018] (Cathode active material) The positive electrode active material contained in the positive electrode material includes a composite oxide of lithium and a transition metal (hereinafter, also referred to as a lithium transition metal composite oxide). Examples of the transition metal include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. Examples of the lithium transition metal composite oxide include layered lithium transition metal composite oxides, spinel type lithium transition metal composite oxides, and olivine type lithium transition metal composite oxides. Specific examples of layered lithium composite oxides include LiCoO2, LiNiO2, LiMnO2, and LiNi a Co b Mn c O2(a+b+c=1), and LiNi a Co b Mn c M dO2 (a+b+c+d=1, M is one or more additive elements selected from Al, Mg, La, Ti, Zn, B, W, Fe, Cr, V, Ru, Cu, Cd, Ag, Y, Sc, Ga, In, As, Sb, Pt, Au, Si, etc.). A specific example of the spinel-type lithium composite oxide is LiMn2O4. A specific example of the olivine type lithium composite oxide is LiMPO4 (M: Fe, Co, Ni, or Mn). The positive electrode active material contained in the positive electrode material may be one type alone or two or more types.

[0019] Among the lithium composite oxides, lithium transition metal composite oxides containing at least one transition metal selected from Ni, Co, and Mn are more preferred, lithium transition metal composite oxides containing Ni and at least one transition metal selected from Co and Mn are even more preferred, and lithium transition metal composite oxides (NCM, nickel cobalt manganese oxide) containing Ni, Co, and Mn as transition metals are even more preferred. The molar ratios of Ni, Co, and Mn contained in the NCM may be, for example, selected from the range of 1:0.1 to 1:1 for the molar ratio of Ni to Co (Ni:Co), and selected from the range of 1:0.1 to 1:1 for the molar ratio of Ni to Mn (Ni:Mn).

[0020] The positive electrode active material may be in a particulate form. The volume average particle diameter of the particulate positive electrode active material is not particularly limited and can be selected, for example, from the range of 5 μm to 30 μm. When the positive electrode active material is a secondary particle that is an aggregate of multiple primary particles, the volume average particle diameter is the volume average particle diameter of the secondary particles. The positive electrode active material contained in the positive electrode material may be one type alone or two or more types. The volume average particle size of the positive electrode active material particles is not particularly limited and can be selected, for example, from the range of 5 μm to 30 μm.

[0021] (Other Ingredients) The positive electrode material may be in the form of a mixture containing components other than the positive electrode active material and the lithium alloy, such as a conductive assistant and a binder, etc. If necessary, a solvent may be added to the mixture to adjust the viscosity of the mixture.

[0022] Specific examples of the conductive assistant include carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes, and graphite. The conductive material contained in the positive electrode material may be of one type alone or of two or more types.

[0023] Specific examples of binders include polyvinylidene fluoride (PVDF), polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, and polymethacrylate. The binder contained in the positive electrode material may be of one type alone or of two or more types.

[0024] (Method of manufacturing positive electrode material) From the viewpoint of suppressing the migration of metal ions originating from the lithium alloy contained in the positive electrode material to the negative electrode side, it is preferable that the method for producing the positive electrode material includes a step of heating a mixture of the positive electrode active material and two or more kinds of lithium alloys at a temperature of 350°C or higher (hereinafter, also referred to as annealing treatment). That is, one embodiment of the present disclosure is Obtaining a mixture containing a positive electrode active material and two or more types of lithium alloys; and heating the mixture at a temperature of 350° C. or higher.

[0025] As shown in the examples described later, a secondary battery manufactured using a positive electrode material obtained by annealing a mixture of a positive electrode active material and two or more kinds of lithium alloys maintains a battery capacity better than a secondary battery manufactured using a positive electrode material obtained without annealing the mixture. This is thought to be due to the fact that the annealing of the mixture causes solid solution diffusion between the positive electrode active material and the lithium alloy, forming a complex. It is thought that the migration of metal ions derived from the lithium alloy to the negative electrode side is suppressed by the lithium alloy being incorporated into the complex.

[0026] The temperature of the annealing treatment is not particularly limited as long as it is 350° C. or higher, and may be 450° C. or higher, 550° C. or higher, or 650° C. or higher. The annealing temperature may be 1000° C. or less, 900° C. or less, or 800° C. or less. The annealing time is not particularly limited and may be selected from the range of 30 minutes to 5 hours. The annealing treatment is preferably carried out in an inert atmosphere such as nitrogen or argon. The mixture after the annealing treatment is preferably in a state in which at least a part of the positive electrode active material and at least a part of the lithium alloy form a complex (such as a solid solution).

[0027] The mixture after the annealing treatment may be subjected to a crushing treatment to form particles. The volume average particle size of the particles obtained by crushing the mixture after the annealing treatment can be selected, for example, from the range of 5 μm to 30 μm. The mixture after the annealing treatment may be further mixed with components such as a conductive assistant and a binder.

[0028] (positive electrode) The positive electrode material of the present disclosure is used as a material for the positive electrode of a lithium ion secondary battery. The positive electrode includes, for example, a current collector and a positive electrode layer disposed on the current collector, and the positive electrode layer includes the positive electrode material of the present disclosure. The positive electrode layer may be disposed on one or both sides of the current collector.

[0029] Examples of materials constituting the current collector of the positive electrode include aluminum, aluminum alloys, nickel, titanium, stainless steel, etc. Examples of the shape of the current collector include foil, mesh, etc.

[0030] The positive electrode layer is disposed on the current collector by, for example, applying a slurry of the positive electrode material to one or both sides of the current collector. If necessary, a pressure treatment may be performed to adjust the density of the positive electrode layer. The thickness of the positive electrode layer is not particularly limited and can be selected, for example, from the range of 10 μm to 100 μm.

[0031] <Lithium-ion secondary battery> The lithium ion secondary battery of the present disclosure has an alloying potential between the positive electrode active material and lithium of 0.5 V (vs. Li / Li + ) or more metal elements.

[0032] The two or more metal elements contained in the positive electrode may be in the form of a simple metal or a lithium alloy. At least a portion of the two or more metal elements contained in the positive electrode may be in a state of forming a complex with the positive electrode active material. The details and preferred embodiments of the positive electrode active material and the two or more metal elements contained in the positive electrode are the same as those of the positive electrode active material and the two or more metal elements contained in the positive electrode material described above.

[0033] The positive electrode in the lithium ion secondary battery of the present disclosure may be obtained using the positive electrode material of the present disclosure described above. Whether or not the positive electrode of a lithium ion secondary battery is obtained using the positive electrode material of the present disclosure can be confirmed, for example, by removing the negative electrode from the lithium ion secondary battery after charging and discharging, and checking whether or not a precipitate of a metal element contained in the positive electrode material is present in the negative electrode. When a precipitate derived from a metal element contained in the lithium alloy used in the positive electrode material of the present disclosure is present in the negative electrode, it can be determined that the positive electrode of this battery was obtained using the positive electrode material of the present disclosure.

[0034] The lithium ion secondary battery of the present disclosure includes, for example, a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. The negative electrode includes, for example, a current collector and a negative electrode layer that is disposed on the current collector and contains a negative electrode active material. Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, soft carbon, and activated carbon, silicon, metallic lithium, lithium alloys, and lithium titanate (LTO). Examples of the material constituting the negative electrode current collector include copper, copper alloy, nickel, titanium, stainless steel, etc. Examples of the shape of the negative electrode current collector include foil, mesh, etc. Examples of the separator include nonwoven fabric, cloth, and microporous film that are mainly made of polyolefin such as polyethylene and polypropylene. The electrolyte may be either liquid or solid. As the liquid electrolyte (electrolytic solution), a known electrolyte such as LiPF6 dissolved in an organic solvent can be used without particular limitation. As the solid electrolyte, a known solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte can be used without particular limitation. EXAMPLES

[0035] The present disclosure will be described in more detail below with reference to examples, but the invention of the present disclosure is not limited to these examples.

[0036] <Preparation of evaluation battery> In the preparation of the batteries in each example, the amount of NCM (LiNi 0.8 Co 0.1 Mn 0.1 O2) and lithium alloys LiB3, Li3Sb, and LiSn, respectively. The amount of each component was adjusted so that the total volume of the positive electrode active material and the lithium alloy was equal in each example.

[0037] In Examples 1 to 3, a mixture of the positive electrode active material and lithium alloy shown in Table 1 was annealed in a nitrogen atmosphere at 700° C. for 2 hours and then crushed to obtain composite particles of the positive electrode active material and lithium alloy. In Examples 4 and 5 and Comparative Examples 1 to 3, the mixture of the positive electrode active material and the lithium alloy shown in Table 1 was not subjected to an annealing treatment.

[0038] A mixture of the positive electrode active material and lithium alloy (93 g), carbon black (4 g) as a conductive additive, PVDF (3 g) as a binder, and a solvent (NMP) were mixed to obtain a slurry of positive electrode material. The obtained positive electrode material was applied to an aluminum foil and dried to obtain a positive electrode. A laminate-type evaluation battery was fabricated using an electrode body formed by laminating the obtained positive electrode, a separator (a polyethylene microporous film), and a negative electrode containing graphite as an active material in this order, and an electrolyte (a mixed solvent of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate containing LiPF6 as an electrolyte).

[0039] <Evaluation of battery performance> The current value at which the positive electrode active material contained in the battery was 210 mA / g was defined as 1C rate, and CCCV charging and CCCV discharging were performed under the following conditions. The obtained CCCV capacity was defined as the capacity of the battery (initial discharge capacity). Lower limit voltage: 2.5V Upper limit voltage: 4.25V Charge / discharge current value: 0.2C End current value: 0.03C After that, the battery was subjected to a cycle test (CC charge / CC discharge). The number of cycles when the CC discharge capacity of the battery reached 40% or less of the initial discharge capacity is shown in Table 1. It can be determined that the greater the number of cycles shown in Table 1, the more effectively the decrease in battery capacity due to repeated charging and discharging is suppressed.

[0040] [Table 1]

[0041] As shown in Table 1, the batteries of Examples 1 to 5, which used two types of lithium alloys as the positive electrode material, showed superior capacity retention rates compared to the batteries of Comparative Examples 1 to 3, which used one type of lithium alloy as the positive electrode material. Among Examples 1 to 5, Examples 1 to 3 in which the mixture of the positive electrode active material and the lithium alloy was annealed showed a better capacity retention rate than Examples 4 and 5 in which the mixture of the positive electrode active material and the lithium alloy was not annealed. Among the batteries in Examples 1 to 3, the battery in Example 1, which used a lithium alloy containing Bi and a lithium alloy containing Sb, showed a particularly excellent capacity retention rate. The reason for this is thought to be that the combination of Bi and Sb exhibits topological insulator-like behavior, suppressing bulk ionization, for example.

[0042] <Evaluation of metal ion release from lithium alloy> After the cycle test, the cell was disassembled and the positive electrode was taken out. A sample solution was prepared from the positive electrode layer using acid, and elemental analysis was performed using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectroscopy). The concentrations of metal elements in the lithium alloy used to prepare the positive electrode are shown in Table 2 as ratios with the initial concentration taken as 100.

[0043] [Table 2]

[0044] As shown in Table 2, in Examples 1 to 3 in which the mixture of the positive electrode active material and the lithium alloy was subjected to an annealing treatment, the residual rate of metal elements derived from the lithium alloy in the positive electrode was higher than in Examples 4 and 5 and Comparative Examples 1 to 3 in which the mixture of the positive electrode active material and the lithium alloy was not subjected to an annealing treatment. The above results suggest that annealing a mixture of a positive electrode active material and a lithium alloy can effectively suppress the migration of metal elements derived from the lithium alloy to the negative electrode side.

Claims

1. A positive electrode active material and two or more types of lithium alloys are included, The two or more types of lithium alloys have an alloying potential with lithium of 0.5 V (vs. Li / Li + ) or more.

2. 2. The cathode material of claim 1, wherein the metallic element is selected from bismuth, tin and antimony.

3. 2. The positive electrode material of claim 1, wherein at least two of the lithium alloys each contain metal elements with different crystal orientations.

4. 2. The positive electrode material according to claim 1, wherein at least a portion of the positive electrode active material and at least a portion of the lithium alloy form a composite.

5. The alloying potential between the positive electrode active material and lithium is 0.5 V (vs. Li / Li + ) or more metal elements.

Citation Information

Patent Citations

  • Lithium secondary battery and manufacturing method thereof

    JP2004335232A

  • Organic electrolyte battery

    JP2010086735A

  • Positive electrode for secondary battery, method for producing same, and lithium secondary battery including same

    JP2021520614A